El control de los sesgos cognitivos en el contexto jurídico procesal: medidas preventivas y correctivas y deberes de responsabilidad epistémica - Bustamante Requena, José Francisco (2024)
This work aims to critically reflect on the problematic relationship between cognitive biases and the procedural legal context, as well as the need to adopt measures to avoid their serious repercussions on judicial decisions. For this purpose, focuses on generality of the studies on the part of previous attempts at improvement are found to be problematic, which are mainly oriented towards the identification of possible actions that should be adopted on a case-by-case basis, in many cases their reasonableness and, above all, being discussed. Its relevance in the task of mitigating or reducing cognitive biases. To overcome these obstacles, two aspects are taken into consideration: the procedures and practices of judicial processes and the preservation of the guarantee and duty of impartiality and how the design of the processes and their dynamics —not always oriented to maximizing impartiality—allow the obtaining decisions compatible with said guarantee. Finally, an intervention scheme is outlined that brings together, on the one hand, the analysis of legal norms and rules (and their impact) on the modification and correction of some legal procedures and practices and, on the other, is complemented by a structured set of duties of epistemic responsibility.